2008
DOI: 10.1007/s10126-008-9105-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gene Expression Profiles of Fenneropenaeus chinensis Challenged with WSSV and Vibrio

Abstract: Microarray technique was used to analyze the gene expression profiles of shrimp when they were challenged by WSSV and heat-inactivated Vibrio anguillarum, respectively. At 6 h post challenge (HPC), a total of 806 clones showed differential expression profile in WSSV-challenged samples, but not in Vibrio-challenged samples. The genes coding energy metabolism enzyme and structure protein were the most downregulated elements in 6 h post WSSV-challenged (HPC-WSSV) tissues. However, a total of 155 clones showed dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Thus, WSSV and YHV viral infections affect the expression of a 4.6-and 2.7-fold, respectively, higher number of shrimp genes than that induced by V. harveyi bacterial infection. This finding is in accordance with the study by Wang et al [9] who reported that the number of WSSV responsive genes in the Chinese shrimp, Fenneropenaeus chinensis, was 1.7-fold higher than that found in Vibrio anguilarum infected shrimps. Comparison of the number of responsive genes between WSSV and YHV infected shrimps revealed a 1.7-fold higher number for WSSV infection.…”
Section: Microarray Analysis Of Differentially Expressed Genes In Patsupporting
confidence: 95%
“…Thus, WSSV and YHV viral infections affect the expression of a 4.6-and 2.7-fold, respectively, higher number of shrimp genes than that induced by V. harveyi bacterial infection. This finding is in accordance with the study by Wang et al [9] who reported that the number of WSSV responsive genes in the Chinese shrimp, Fenneropenaeus chinensis, was 1.7-fold higher than that found in Vibrio anguilarum infected shrimps. Comparison of the number of responsive genes between WSSV and YHV infected shrimps revealed a 1.7-fold higher number for WSSV infection.…”
Section: Microarray Analysis Of Differentially Expressed Genes In Patsupporting
confidence: 95%
“…However, few reports suggest that FABPs is associated with immunity [1]. For example, differential expression of L-FABP and H-FABP was observed in Fenneropenaeus chinensis challenged with white spot syndrome virus (WSSV) and Vibrio [26]. Suppression subtractive hybridization results showed upregulated expression of FABP in the hepatopancreas of WSSV resistant and susceptible shrimp innate immunity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the response of shrimps upon Vibrio infection has been reported only at the transcriptional level [5-7]. Indeed, several groups of V. harveyi -responsive genes in shrimps have been identified.…”
Section: Introductionmentioning
confidence: 99%